Employee satisfaction and performance based on organizational culture, work motivation, and compensation - Purba, Christiady; Ilmi, Zainal; Irwansyah, (International Journal of Psychosocial Rehabilitation, 2020)
This study tries to investigate the relationship between organizational culture, work motivation, and compensation for job satisfaction and employee performance at PT. Surya Hutani Jaya (Muara Kaman, Indonesia). This company is a company that manages industrial park forests (HTI), which operationally produces forest wood cost in three ways, namely seeding, planting, and harvesting. The relationship between company management and its employees is very important when individuals work to make a major contribution to the progress of the company's vision and mission. The study used a survey approach that was obtained directly through a questionnaire distributed to respondents (in this case, employees) at PT. Surya Hutani Jaya. With a purposive sampling technique, a sample size of 100 was determined. We processed the data using the SEM-PLS model through SmartPLS 3.0. Empirical findings prove that organizational culture and compensation have a positive and significant effect on job satisfaction, while work motivation has a negative and insignificant effect on job satisfaction. From the second model, work motivation and compensation have a positive and significant effect on employee performance. On the other hand, organizational culture and job satisfaction have a positive and insignificant effect on employee performance. The value of the originality of this study lies in the novelty of studies that have never been done before with objects, samples, and the use of variables and the similarity of analysis results.